ПРИМЕНЕНИЕ ТВОРЧЕСКИХ ЭЛЕМЕНТОВ В ДИСТАНЦИОННОМ ОБУЧЕНИИ СТУДЕНТОВ ТЕХНИЧЕСКОГО ВУЗА - Мишенина, И.В.; Худоян, М.В.; Темираев, К.Б. (SCIENCE and SOCIETY, 2025)
The article examines the role of creative elements in enhancing the quality of distance learning for technical university students. A pedagogical experiment was conducted at the North Caucasus Mining and Metallurgical Institute (GTU) during 2020–2024, involving 800 first- and second-year students. The ARCS motivation model by John Keller and an educational olympiad environment were implemented. The results demonstrated a statistically significant increase in students’ motivation, cognitive flexibility and originality in the experimental groups. The findings confirm the effectiveness of integrating creative learning strategies into distance engineering education.
Keywords: distance learning; ARCS model; student motivation; olympiad environment; engineering education; creative thinking